PSIV-27 Late-Breaking: Effects of substitution of corn with brown rice on growth performance, nutrient digestibility, and microbiota of growing-finishing pigs. (7th December 2018) - Kim, B; Kim, S; Kim, J; Lee, J; Kang, J; Mun, D; Baek, J; Kim, S; Choe, J; Song, M
Abstract: The experiment was conducted to investigate effects of brown rice as alternatives on growth performance, nutrient digestibility, and gut microbiota of growing-finishing pigs. A total of 50 growing pigs (23.80 ± 2.96 kg BW) were randomly allotted to 2 dietary treatments (5 pigs/pen; 5 replicates/treatment) in a randomized complete block design (block = BW). Dietary treatments were a grower-finisher diet based on corn-soybean meal (CON) and the other diets formulated by replacing corn with 100 % of brown rice (BR). Pigs were fed respective dietary treatments for 12 weeks during growing and finishing periods, respectively. For the last week of experiment period, pigs were fed respective dietary treatments containing 0.2 % chromic oxide as an indigestible marker. Fecal samples were collected from randomly selected 1 pig in each pen daily for the last 3 d after the 4 d adjustment period. Measurements were growth performance, nutrient digestibility by an index method and gut microbiota by metagenomic analysis with pyrosequencing. Data were analyzed using the PROC GLM procedure of SAS. The pyrosequencing data was analyzed using CLcommunity program. There were no differences on growth performance and nutrient digestibility during overall experimental period between dietary treatments. No differences were detected on gut microbiota of growing pigs between dietary treatments. Finishing pigs fed BR increased (P < 0.05) phylum Bacteroidetes and genus Barnesiella in gut microbiota compared with those fed CON. However, decreased (P < 0.05) phylum Firmicutes and genus Lactobacillus and Streptococcus in gut microbiota were observed in finishing pigs fed BR compared with those fed CON. In conclusion, substitution of corn with brown rice in growing-finishing diets may modulate gut microbiota of pigs without no negative effects on growth performance.